РОЛЬ И ФОРМИРОВАНИЕ ОСНОВНЫХ РАСТИТЕЛЬНЫХ СООБЩЕСТВ СОЛОНЧАКОВ НИЗОВЬЕВ АМУДАРЬИ - Кенесбаева, Н.М. (SCIENCE and SOCIETY, 2025)
The article examines the features and role of the formation of the main plant communities of salt marshes in the lower reaches of the Amu Darya, as well as provides information on the scheme of formation of halophytic communities of salt marshes in the lower reaches of the Amu Darya, the role of halophytic plants in maintaining ecosystem stability.